An Analysis of Sub-District Education Officers’ Practices in Supervising Curriculum Implementation at Primary Schools in Bangladesh - Sathi Alam, Shahima (Edu-Ling: Journal of English Education and Linguistics, 2024)
This study examines the practices of Education Officers (EOs) in overseeing curriculum implementation and teaching activities of primary school teachers in Bangladesh. The aim of the study is to identify the challenges faced by the EOs and how they mitigate them in the contexts of bridging the knowledge gap and their impact on educational quality. Data was elicited from a group of purposive samples in the form of experienced EOs from the district. The study managed to explore how EOs assist teachers in implementing academic curriculum, policies and enhance teaching and learning outcomes through interviews and field observations. The findings showed that the UEOs faced a multitude of challenges which stem from a number of internal and external sources. They had to rely on a number of strategies to mitigate the challenges to ensure that they could undertake their   routine tasks well and achieve the objectives of their jobs. Using effective communication, empathy by putting themselves in the teachers’ shoes, walk the talk by showing rather than just telling and using available ICT and social media educational tools are among the strategies utilized by the EOs. These useful insights will provide policymakers with valuable insights into strategies to increase EOs' effectiveness and strengthen Bangladesh's educational system. In conclusion the EOs, the higher authorities, and the whole education fraternity in the country must put concerted efforts towards education albeit all the resources and logistical shortcomings that hamper teachers and schools.